NEW DATA IN THE RESEARCH OF SETTLEMENTS OF THE SAKA TIME IN CENTRAL KAZAKHSTAN - А.З. Бейсенов (Теория и практика археологических исследований, 2021)
The article is devoted to an overview of the results of new studies of the Saka era settlements discovered in the eastern regions of Central Kazakhstan. The source base of modern research was made up of over 70 settlements found over the past 20 years. The author attributes these settlements to the tasmola culture of Central Kazakhstan and dates them within the framework of the 8th — 5th centuries BC. Archaeozoological, traceological, and carpological analyzes are being carried out based on the materials from the excavations of the Kulzhan-1 and Abylai settlements and other sites carried out in recent years. According to the author, the settlements of Central Kazakhstan of the Saka era were the winter habitats of the tribes of the Tasmola culture. Materials from over 50 Kazakh wintering sites make it possible to draw ethnographic data. A comparative study of these sites has shown that the topography of the Kazakh wintering grounds and Saka settlements coincide.